Influenza A Virus Nucleoprotein Activates the JNK Stress-Signaling Pathway for Viral Replication by Sequestering Host Filamin A Protein - Sharma, Anshika; Batra, Jyoti; Stuchlik, Olga; Reed, Matthew S.; Pohl, Jan; Chow, Vincent T. K.; Sambhara, Suryaprakash; Lal, Sunil K. (Frontiers in Microbiology, 2020)
Influenza A virus (IAV) poses a major threat to global public health and is known to employ various strategies to usurp the host machinery for survival. Due to its fast-evolving nature, IAVs tend to escape the effect of available drugs and vaccines thus, prompting the development of novel antiviral strategies. High-throughput mass spectrometric screen of host-IAV interacting partners revealed host Filamin A (FLNA), an actin-binding protein involved in regulating multiple signaling pathways, as an interaction partner of IAV nucleoprotein (NP). In this study, we found that the IAV NP interrupts host FLNA-TRAF2 interaction by interacting with FLNA thus, resulting in increased levels of free, displaced TRAF2 molecules available for TRAF2-ASK1 mediated JNK pathway activation, a pathway critical to maintaining efficient viral replication. In addition, siRNA-mediated FLNA silencing was found to promote IAV replication (87% increase) while FLNA-overexpression impaired IAV replication (65% decrease). IAV NP was observed to be a crucial viral factor required to attain FLNA mRNA and protein attenuation post-IAV infection for efficient viral replication. Our results reveal FLNA to be a host factor with antiviral potential hitherto unknown to be involved in the IAV replication cycle thus, opening new possibilities of FLNA-NP interaction as a candidate anti-influenza drug development target.